Molecular identification of immature stages of medically important fly species, Puducherry, South India: a preliminary study - Bhuvaneshwaran, Sudha; Padmanaban, Visa Shalini; Radja, Ranjana Devi; Anandan, Gayathri; Venkatesan, Shakila; Semalaiyappan, Janani; Kumar, Ashwani; Kuttiatt, Vijesh Sreedhar (Frontiers in Insect Science, 2025)
Flies and maggots are of medical importance, and it is often necessary to identify them at species level. Conventionally, this is carried out based on morphological features using taxonomic keys. However, identification of maggots based on morphology is difficult and required entomological expertise is often lacking in clinical settings. Molecular methods can be an alternative to morphology-based identification and find special application when only tiny pieces of specimens are available especially in cases of human myiasis. In this preliminary study, we explored the utility of mitochondrial COI gene based molecular method, for identifying immature stages of certain medically important flies captured from the field in Puducherry, India. Maggots were captured from different locations in Puducherry using rotten fish and kitchen waste as baits and a 700 bp segment of the COI gene was amplified and genetic relationship was assessed by performing haplotype network analysis. High quality sequences were available for 11 specimens and were subjected to BLAST analysis to identify matches from the database for identification of the species. The identified maggots belonged to Sarcophaga peregrina (Robineau-Desvoidy, 1830), Hemipyrellia ligurriens (Wiedemann, 1830) and Chrysomya megacephala (Fabricius, 1794). This study generated representative molecular sequence data for two less studied fly species of medical importance, S. peregrina and H. ligurriens from South India. In future, there is a need for further detailed molecular studies on flies in the diverse epidemiological and geographic settings in India with a view to identify cryptic species and new haplotypes.